Analisis Pelaksanaan Pengenalan Lapangan Persekolahan FKIP Universitas Riau Bidang Fisika di MA Hasanah - Cindy Gusvita Hamdani; Rati Rahayu (Jurnal Humaniora dan Ilmu Pendidikan, 2023)
Purpose: Based on the background and the number of formulations above, the goal to be achieved is to find out the process of implementing the School Field Introduction (PLP) Faculty of Teacher Training and Education (FKIP) University of Riau at MA Hasanah School Pekanbaru. For a factual educational experience in applying knowledge, attitudes and skills that can support the achievement of four competencies, namely pedagogic competence, competence competence, social competence and professional competence in the formation of professional and characterized student teacher candidates. Methodology: This type of research uses descriptive qualitative, research design, data collection, reduction and drawing conclusions. Results: The study revealed that the implementation of the School Field Introduction (PLP) at MA Hasanah Pekanbaru was quite good. It can be seen from the experiences gained by students by prospective teacher students including experience in teaching, compiling syllabus and lesson plans, as well as knowing more about the MA Hasanah Pekanbaru school. Limitations: Data collection techniques on the research background only by interview. Contribution: The existence of this research can be useful as input and improvement material for the implementation of PLP next year so that it can be even better than before.